Strategi Deterrence dalam Pertunjukan Kekuatan: Analisis Parade Militer China di Era Modern - Dian Trianita Lestari; Harnina Ridwan; Shinta Arjunita Saputri (CV. ITTC INDONESIA, 2026)
This article examines deterrence methods in current Chinese military parades, concentrating on their use as power shows, political symbols, and international diplomacy. Military parades are viewed not just as official ceremonies, but as an essential component of defense strategy and political communication. By displaying current defense equipment like as hypersonic missiles, air defense systems, and advanced military technology, China presents a convincing message of military capacity to both domestic and international audiences. This represents two types of deterrence: punishment (the danger of damaging retaliation) and denial (the ability to prevent an opponent's attack). In addition to their outward function, military parades have a significant domestic political component. Parades promote the legitimacy of Xi Jinping's leadership and the Chinese Communist Party by telling a story of national awakening (the China Dream), instilling collective pride and strengthening social solidarity. Internationally, parades elicit varied reactions: Western countries are cautious and see them as an indication of military expansion, whereas Global South countries see them as a symbol of the development of non-Western powers. This study employs a qualitative descriptive-analytical methodology, with a literature review as the data gathering method. According to the research findings, Chinese military parades serve three purposes: strategic deterrent, a domestic political symbol, and a symbolic diplomatic weapon. These findings suggest that military parades play an important role in comprehending modern defense policy, political legitimacy, and regional and global security dynamics.